數位典藏與學習之學術與社會應用推廣計畫---子計畫三：推動數位典藏人文社會經濟產業發展之人文與社會發展子計畫 - 李峻德; Lee Jiunde Jim (My University, 2011)
本子計畫為「數位典藏與學習之學術與社會應用推廣計畫」分項計畫下之「人文與社會發 展子計畫」（以下簡稱本子計畫）。本子計畫企圖結合學術研究、弱勢族群及第三部門的力量， 擴大數位典藏計畫的社會參與，以增進數位典藏之共享與傳佈。本計畫包括三大重點項目：（一） 數位落差、公民與社區參與數位典藏；（二）數位典藏之資訊倫理與數位人權面向；（三）數 位典藏推廣使用介面改善與社會影響。 在實施策略上，本計畫採學術研究與應用實務並進，有如下之具體工作計畫。首先，透過 與本子計畫之公開徵選計畫之間的有機聯繫與整合，與社區大學、偏鄉原住民部落、數位機會 中心及公民團體合作，落實數位典藏之民間參與、紀錄、推廣與應用，務求縮減數位落差，強 化偏鄉弱勢族群及公民團體近用數位典藏成果的機會。再者，促進數位典藏之共享與傳佈的同 時，必須強化數位典藏在資訊倫理和數位人權面向的操作與實踐，因此本計畫以數位典藏資料 庫為對象，發展本土案例與評價系統，透過數位人權的評價系統檢視及修正數位典藏成果，藉 以協助數位典藏傳播者與使用者培養資訊倫理與數位人權意識，從而達到數位典藏的人文與社 會發展目標。最後，為強化數位典藏與使用者的日常生活的聯繫，本計畫採用人機介面研究， 透過情境探索、使用性測試及情緒測量等資料，分析使用者運用數位典藏的資源過程中的問題 及關鍵影響因素，並了解使用者如何詮釋、處理及因應，相關資料可作為解決數位典藏推廣困 境的依據，並減少數位落差之社會負面影響。 有鑑於本計畫所關注的弱勢族群及偏鄉地區，在去年莫拉克風災受創甚深，基於數位典藏 應扣連弱勢族群的需求與發展，本計畫過去一年來不可免地在參與、推廣活動的設計上與災後 重建、防災等議題結合，新年度的計畫也將繼續在災害議題上著力，推廣數位典藏與裨益偏鄉 社會發展。簡言之，本計畫期使數位典藏貼近公民需求，突破數位落差及使用介面之限制，進 而邁向並最終充分實現資訊倫理及數位傳播人權願景，拓展數位典藏的人文與社會發展效應。

Enriching local digital archives is the important means to reduce the digital divide according to the main goal of National Digital Archives Program. The main target of this project is to improve the access and use of digital archives of public resource and to solve the problem of the digital divide and enhance digital human right. This project revolves around three core tasks: to promote citizen participation and bridge the digital divide, to enhance information ethics and digital human rights, and to improve the interface of digital archive database and expand its social influence. The detailed strategies are as follows. Firstly, the project cooperates with the civil sector and minority groups in the process of making and applying digital archives. Through the cooperation and participation, people’s awareness of digital archive and their digital capability are enhancing and the results of empowerment are expected. The efforts have its influence on reducing the digital divide and enhancing the sharing and distribution of digital archives. Secondly, the project adds an important dimension of information ethics and digital right in the need of digital archive promotion. By building the evaluation system from the perspective of human rights, this project can help to amend and improve the design and use of digital archive and cultivate the awareness of human rights among archive producers and users. Thirdly, to extend the accessibility of digital archives, the project believes that a digital archive platform should offer a qualified user interface. Thus, based on the context of digital archive databases, web applications, and internet services, the project is to systematically establish user profiles, reveal users’ needs, and generate possible interface functions. The results of relevant analysis are expected to become valuable references to improve the interaction design of future digital archive platforms and expansion of the social impact. In addition, in the past year this project has taken efforts in weaving digital archive into the reconstruction of post-Typhoon Moraket which hit Taiwan and caused a serious disaster in August 2009. This project has worked in remote rural areas to make digital archive accessible to the disadvantaged groups, therefore the making and promotion of digital archive should be connected to their current lives and concerns. This year, this project will put lots resources in linking digital archive and natural disaster and its prevention and reconstruction.This shift of concern will make digital archive more meaningful to the disadvantaged people and bridge the digital divide in the long term.
The Cultural and Social Development Project of Cultural, Academic, Socio-Economic, and Educational Promotions and Applications for National Digital Archives Program
Keywords: 人機介面; 公民參與; 傳播權利; 資訊倫理; 數位人權; 數位典藏; 數位落差; communication rights; contextual inquiry; digital archive; digital divide; digital human rights; information ethics; user interface